2015
DOI: 10.1242/dmm.022103
|View full text |Cite
|
Sign up to set email alerts
|

Non-muscle myosin II in disease: mechanisms and therapeutic opportunities

Abstract: The actin motor protein non-muscle myosin II (NMII) acts as a master regulator of cell morphology, with a role in several essential cellular processes, including cell migration and post-synaptic dendritic spine plasticity in neurons. NMII also generates forces that alter biochemical signaling, by driving changes in interactions between actin-associated proteins that can ultimately regulate gene transcription. In addition to its roles in normal cellular physiology, NMII has recently emerged as a critical regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 320 publications
1
115
1
1
Order By: Relevance
“…This positive feedback mechanism on Src would be expected to cause the subsequent decrease in stress fibre-dependent contractility allowing for cell migration. However, we cannot exclude that the effect of inhibiting Myosin II activity on ERK-dependent cell proliferation is independent of the polarized stress fibres by EVL, as Myosin II activity controls several essential cellular processes47.…”
Section: Discussionmentioning
confidence: 94%
“…This positive feedback mechanism on Src would be expected to cause the subsequent decrease in stress fibre-dependent contractility allowing for cell migration. However, we cannot exclude that the effect of inhibiting Myosin II activity on ERK-dependent cell proliferation is independent of the polarized stress fibres by EVL, as Myosin II activity controls several essential cellular processes47.…”
Section: Discussionmentioning
confidence: 94%
“…Nonmuscle myosin II is a major contributor to cellular organisation and regulation. Myosins are able to crosslink and bundle actin filaments to promote contraction forces capable of deforming cell membranes in processes such as cell migration and phagocytosis (Newell‐Litwa, Horwitz, & Lamers, ). Prior studies by Stradal and colleagues characterised a RhoA/Myosin II‐dependent pathway of actin rearrangement during S .…”
Section: Resultsmentioning
confidence: 99%
“…Blebbistatin (BLEB) has been discovered with the aid of a high-throughput molecule screen for inhibitors of nonmuscle myosin II (Straight et al 2003). Furthermore, it was demonstrated that BLEB inhibits both nonmuscle and muscle myosins (Newell-Litwa et al 2015). Moreover, it was demonstrated that BLEB inhibiting potential is higher toward the SM-B (which is present in higher amounts in the urinary bladder (Andersson and Arner 2004)) compared to the SM-A type (Rhee et al 2006) (which is found in lower abundance in the bladder (Andersson and Arner 2004)).…”
Section: Introductionmentioning
confidence: 99%